Bill prioritisation and bill payment orientation in the developing country context. (1st April 2019) - Knight, Joseann; Carrington, Donley
Adverse economic conditions often result in bill payment default by consumers and compromised accounts receivable for service providers. Default is especially problematic in developing countries where the average consumer has less spending power. Yet, international service brands know very little about the debt attitudes of developing country consumers. Using Maslow's hierarchy of needs framework, this paper examines whether consumers adopt a hedonic or a utilitarian approach to bill prioritisation activity. Knowing the relative importance of one's service better equips the service provider to develop compelling communications to support or to enhance consumers' perceptions if need be. The study also introduces service bill payment orientation (SBPO) which measures how consumers view bill payments in general, thereby contributing to the newly emerging literature on the debt attitudes of developing country consumers. The findings of the study point to a utilitarian bill payment approach and suggest that SBPO may be more a consequence of national culture than of demographic differences between consumers.